Exclusion versus preservation of the left atrial appendage in rheumatic mitral valve surgery. Issue 23 (6th May 2020) - Kim, Wan Kee; Kim, Ho Jin; Kim, Joon Bum; Jung, Sung Ho; Choo, Suk Jung; Chung, Cheol Hyun; Lee, Jae Won
Abstract : Objectives: This study aimed to evaluate the impact of left atrial appendage exclusion on clinical outcomes in patients with atrial fibrillation (AF) undergoing rheumatic mitral surgery. Methods: We retrospectively reviewed 1226 consecutive patients with AF (54.5±11.6 years; 68.2% females) who underwent rheumatic mitral valve (MV) surgery from 1997 to 2016. The left atrial appendage was preserved in 836 (68.2%) and excluded in 390 (31.8%) patients. Surgical AF ablation was performed in 506 (60.5%) and 304 (77.9%) patients with preserved and excluded left atrial appendage, respectively. For baseline adjustment, propensity matching was used. Results: During a median follow-up of 63.4 months (IQRs, 20–111 months), there were no significant intergroup differences in the risks of mortality (2.77% vs 3.03%/patient-years) and thromboembolic events (0.91% vs 1.02%/patient-years). In the 258 pairs of propensity-score matched patients, death (2.77% vs 3.03%/patient-years) and thromboembolism (1.36% vs 0.82%/patient-years) outcomes were comparable for both groups. In a subgroup undergoing ablation (n=810), there were no significant differences in the adjusted risks of death (HR, 0.67; 95% CI, 0.34 to 1.32) and thromboembolism (HR, 0.47; 95% CI, 0.18 to 1.26). In a subgroup not undergoing ablation (n=416), however, left atrial appendage preservation tended to have higher adjusted risks for death (HR, 2.24; 95% CI, 0.98 to 5.13) and thromboembolism (HR, 4.41; 95% CI, 0.97 to 20.1). Conclusions: Left atrial appendage preservation did not seem to have greater risks of adverse clinical events in patients with AF undergoing rheumatic MV surgery particularly when ablation procedure is combined.